It is currently 19 Sep 2017, 19:15

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

Find the the sum of the first 20 terms of this series which

  post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
VP
VP
User avatar
Joined: 13 Jun 2004
Posts: 1114

Kudos [?]: 50 [0], given: 0

Location: London, UK
Schools: Tuck'08
Find the the sum of the first 20 terms of this series which [#permalink]

Show Tags

New post 13 Mar 2005, 19:19
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Find the the sum of the first 20 terms of this series which begins this way : –1^2 + 2^2 – 3^2 + 4^2 – 5^2 + 6^2...

(a) 210
(b) 330
(c) 519
(d) 720
(e) 190

Last edited by Antmavel on 13 Mar 2005, 20:56, edited 1 time in total.

Kudos [?]: 50 [0], given: 0

GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 07 Jul 2004
Posts: 5039

Kudos [?]: 424 [0], given: 0

Location: Singapore
 [#permalink]

Show Tags

New post 13 Mar 2005, 20:18
antmavel, do you meant 1^2 in your question or something else?? The power is missing from your question.

Kudos [?]: 424 [0], given: 0

GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 07 Jul 2004
Posts: 5039

Kudos [?]: 424 [0], given: 0

Location: Singapore
 [#permalink]

Show Tags

New post 13 Mar 2005, 20:25
I assume you're missing out a ^2 for base '1'.
The series will work out to be an arithmetic progression with 10 terms, and a common difference of 4. The sum will therefore be 10/2(2(3) + 9(4)) = 210 (A)

Kudos [?]: 424 [0], given: 0

Manager
Manager
avatar
Joined: 13 Oct 2004
Posts: 236

Kudos [?]: 15 [0], given: 0

 [#permalink]

Show Tags

New post 13 Mar 2005, 20:33
sum of squares = n*(n+1).(2n+1) / 6

summing all the +ve nos : 2^2+4^2+6^2...= 4(1^2+...+10^2) = 1540
sum of all -ve nos = (sum of squares upto 20) - 1540 = 1330

Sum asked = 1540 - 1330 = 210.

Kudos [?]: 15 [0], given: 0

VP
VP
avatar
Joined: 18 Nov 2004
Posts: 1431

Kudos [?]: 43 [0], given: 0

 [#permalink]

Show Tags

New post 13 Mar 2005, 20:39
"A"

series will be:

-1+ 2^2-3^2+4^2....

3,7,11,15,19,23....of 10 terms...of equally spaced numbers with diff of 4

Avg = (19+23)/2 = 21

21 = (SUM)/10

SUM = 210

Kudos [?]: 43 [0], given: 0

VP
VP
User avatar
Joined: 13 Jun 2004
Posts: 1114

Kudos [?]: 50 [0], given: 0

Location: London, UK
Schools: Tuck'08
 [#permalink]

Show Tags

New post 13 Mar 2005, 20:57
ywilfred wrote:
antmavel, do you meant 1^2 in your question or something else?? The power is missing from your question.


oooops :oops: sorry, I've modified it...

you were right, OA is A

Kudos [?]: 50 [0], given: 0

VP
VP
User avatar
Joined: 25 Nov 2004
Posts: 1482

Kudos [?]: 121 [0], given: 0

Re: sum of terms [#permalink]

Show Tags

New post 13 Mar 2005, 21:46
A

=-1+4-9+.................. -361+400
=3+7+11+...................+39
a1=3
d=an-a1=7-3=11-7=4
sum of the series = a1+a2+a3+a4+....+a10=210

Kudos [?]: 121 [0], given: 0

SVP
SVP
User avatar
Joined: 03 Jan 2005
Posts: 2232

Kudos [?]: 368 [0], given: 0

Re: sum of terms [#permalink]

Show Tags

New post 13 Mar 2005, 22:19
I'd do it this way:
2^2-1^2=(2+1)(2-1)
4^2-3^2=(4+3)(4-3)
...
Therefore S=1+2+3+4+...19+20=(1+20)*20/2=210

Kudos [?]: 368 [0], given: 0

VP
VP
avatar
Joined: 30 Sep 2004
Posts: 1480

Kudos [?]: 403 [0], given: 0

Location: Germany
 [#permalink]

Show Tags

New post 14 Mar 2005, 03:17
+ nos=> first+last/2=>(4+400)/2*10=>2020
- nos=> (-1+(-361))/2*10=>1810
2020-1810=210

Kudos [?]: 403 [0], given: 0

Manager
Manager
avatar
Joined: 15 Feb 2005
Posts: 246

Kudos [?]: 8 [0], given: 0

Location: Rockville
 [#permalink]

Show Tags

New post 14 Mar 2005, 13:04
i used the average of the 5th and 6th term and multiplied it by the total number of terms...210

Kudos [?]: 8 [0], given: 0

Director
Director
User avatar
Joined: 21 Sep 2004
Posts: 607

Kudos [?]: 35 [0], given: 0

Re: sum of terms [#permalink]

Show Tags

New post 14 Mar 2005, 14:49
HongHu wrote:
I'd do it this way:
2^2-1^2=(2+1)(2-1)
4^2-3^2=(4+3)(4-3)
...
Therefore S=1+2+3+4+...19+20=(1+20)*20/2=210

great way to do :)

Kudos [?]: 35 [0], given: 0

Senior Manager
Senior Manager
avatar
Joined: 02 Feb 2004
Posts: 344

Kudos [?]: 72 [0], given: 0

 [#permalink]

Show Tags

New post 19 Mar 2005, 14:08
[quote="ywilfred"]I assume you're missing out a ^2 for base '1'.
The series will work out to be an arithmetic progression with 10 terms, and a common difference of 4. The sum will therefore be 10/2(2(3) + 9(4)) = 210 (A)[/quote

I like this formula. Can somebody pls explain?

Kudos [?]: 72 [0], given: 0

Director
Director
User avatar
Joined: 25 Jan 2004
Posts: 721

Kudos [?]: 28 [0], given: 0

Location: Milwaukee
Re: sum of terms [#permalink]

Show Tags

New post 20 Mar 2005, 01:20
HongHu wrote:
I'd do it this way:
2^2-1^2=(2+1)(2-1)
4^2-3^2=(4+3)(4-3)
...
Therefore S=1+2+3+4+...19+20=(1+20)*20/2=210



I was really lost on this one. Thanks HongHu
_________________

Praveen

Kudos [?]: 28 [0], given: 0

Director
Director
avatar
Joined: 18 Feb 2005
Posts: 668

Kudos [?]: 6 [0], given: 0

Re: sum of terms [#permalink]

Show Tags

New post 20 Mar 2005, 06:27
HongHu wrote:
I'd do it this way:
2^2-1^2=(2+1)(2-1)
4^2-3^2=(4+3)(4-3)
...
Therefore S=1+2+3+4+...19+20=(1+20)*20/2=210


Elegance par excellence.......is your solution !!!!

Kudos [?]: 6 [0], given: 0

Manager
Manager
avatar
Joined: 24 Jan 2005
Posts: 217

Kudos [?]: 13 [0], given: 0

Location: Boston
 [#permalink]

Show Tags

New post 20 Mar 2005, 16:46
I did it like this
Add 2^2 + 4^2 + 6^2... and subtract 2^2 + 4^2 + 6^2...

So the series becomes - (1^2 + 2^2 + 3^2...20^2) + 2 ( 2^2 + 4^2 + 6^2..+20^2)

= - n(n+1)(2n+1)/6 (Here n = 20) + 2*4*n(n+1)(2n+1)/6 (Here n = 10)

= -410*7 + 440*7 = 210

Kudos [?]: 13 [0], given: 0

  [#permalink] 20 Mar 2005, 16:46
Display posts from previous: Sort by

Find the the sum of the first 20 terms of this series which

  post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.